2019
DOI: 10.1111/jfd.13003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of round goby viral haemorrhagic septicaemia outbreak in New York

Abstract: Eleven viral haemorrhagic septicaemia virus (VHSV) genotype IVb isolates were sequenced, and their genetic variation explored to determine the source of a VHS outbreak on the eastern shore of Cayuga Lake. An active fish kill of round gobies (Neogobius melanostomus, Pallas) was intensively sampled at King Ferry, NY and nearby Long Point State Park in May 2017. Gross lesions observed on 67 moribund round gobies and two rock bass (Ambloplites rupestris, Rafinesque) included moderately haemorrhagic internal organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(55 reference statements)
0
5
1
Order By: Relevance
“…A more recent analysis of 11 other VHSV‐IVb whole‐genome positives, including five from the 2017 Cayuga Lake outbreak and four from a 2017 round goby kill at Long Point State Park, NY by Getchell et al. (2019), discerned 379 SNPs, with 123 being nonsynonymous (33.4%), which also is higher than ours for both and might again reflect sampling size or a mutation rate difference. Similar to our results, a Zika Virus study found 16% nonsynonymous changes among 1,030 SNPs across 110 whole genomes (Metsky et al., 2017), close to the proportion we identified here in the partial G ‐gene sequences and across the entire VHSV‐IVb genome.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…A more recent analysis of 11 other VHSV‐IVb whole‐genome positives, including five from the 2017 Cayuga Lake outbreak and four from a 2017 round goby kill at Long Point State Park, NY by Getchell et al. (2019), discerned 379 SNPs, with 123 being nonsynonymous (33.4%), which also is higher than ours for both and might again reflect sampling size or a mutation rate difference. Similar to our results, a Zika Virus study found 16% nonsynonymous changes among 1,030 SNPs across 110 whole genomes (Metsky et al., 2017), close to the proportion we identified here in the partial G ‐gene sequences and across the entire VHSV‐IVb genome.…”
Section: Discussioncontrasting
confidence: 62%
“…Getchell et al. (2019) also reported polymorphisms at single NT positions in some isolates from the Cayuga Lake 2017 outbreak. Here, we found no evidence of multiple haplotypes within a single individual.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Given the presence of VHSV-IVb throughout the Great Lakes watershed there is tangible risk to all farmed fish in the region [22,23]. VHSV-IVa/b are reported to cause mild to modest disease in rainbow trout (Oncorhynchus mykiss) [24,25], but disease kinetics and mortalities may be comparable to those seen in yellow perch (Perca flavescens) and round gobies (Neogobius melanostomus), which are highly susceptible to this pathogen [26][27][28]. Additional challenge studies show that VHSV-IVb can cause significant morbidity and mortality in rainbow trout [29,30].…”
Section: Introductionmentioning
confidence: 99%